Characterization, microstructure properties and impurities removal of treated rice husk ash (TRHA) as supplementary cementing material (SCM) in concrete using hydrochloric acid pretreatment process - Saad, Siti Asmahani; Nuruddin, Muhd Fadhil; Shafiq, Nasir; Ali, Maisarah (AENSI, 2015)
Recently, the need towards production of environmental friendly and excellent performance cementitious material has been outlined properly. Based on extensive researches done since 1970s, it is proven that rice husk ash (RHA) is silica-rich material and hence categorized as pozzolans in concrete. Nevertheless, the usage of this material in real construction industries is still under expectation. This is simply due to instability of the chemical components, especially amorphous silica content in the material after burning process. The aim of this paper is to present the characteristics and unwanted metal leaching evaluation of treated rice husk ash (TRHA) to be utilized as supplementary cementing material (SCM) in concrete. In this regard, raw rice husk was treated by adopting hydrochloric acid (HCl) pretreatment method prior to burning process. Several tests have been conducted to analyze the chemical compositions, specific surface are (SSA), microstructure properties and concentration of alkali metalremoval of TRHA and compared to non-treated rice husk ash (NTRHA). In this paper, the effect of soaking time in acid solution from 1 to 4 hours is also presented and discussed accordingly.